Improved MRV of GHG emissions in the livestock sector - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
Key partners come together in Addis Ababa to develop robust systems for measurement, reporting and verification of emissions from Ethiopia’s livestock sector.